Protein stability study with respect to mutation in Brassica juncea, Brassica rapa and Brassica napus - Simran Kotwal,; SN Malode, (Journal of Oilseed Brassica, 2026)
In the present study Brassica juncea, B. rapa, B. napus and their accessions lines of M5 generation were analyzed in M6generation for protein profiling through sodium dodecyle sulphate (SDS)–PAGE. SDS–PAGE with some modificationsthe resolution capacity of small molecular mass protein less than 20 kDa were separable with the used technique. Thebanding pattern of protein of rapeseed-mustard and their accessions have variable molecular, weight bands extend from9 to 65 kDa. The total 50 bands obtained in which 43 bands were polymorphic, 7 bands were unique and 7 weremonomorphic in rapeseed-mustard and their accessions. The B. juncea var. Bio-902, 3321, 666, GPT1 has unique proteinbands. The value of similarity among different cultivars fluctuates between 0.26 to 1.0. The highest similarity value wasobserved 0.68 in B. napus. The lowest similarity value was recorded 0.26 in B. juncea accession(427-2). After studying the M6 generation of rapeseed-mustard soluble seed protein revealed some differences amongthe species in terms of the number, position and intensity of bands, while accession discrimination based on SDS-PAGEwas also done. Based on polymorphic and unique bands there was 86 % polymorphism among the rapeseed-mustardand their accessions.